Proteolytic properties of Funastrum clausum latex - Morcelle del Valle, Susana Raquel (2004)
As part of a screening of latex endopeptidases from plants growing in Argentina, the presence of proteolytic activity in the latex of Funastrum clausum stems is reported. The proteases present in the crude extract showed the main characteristics of the cysteine proteolytic class, i.e. optimum pH at alkaline range, isoelectric point (pI) higher than 9.0, and inhibition of proteolytic activity by thiol blocking reagents. A remarkable thermal stability was also evident in the crude extract. Endosterolytic preference tried on p-nitrophenyl esters of N-a-carbobenzoxy-L-amino acids was higher for the alanine, asparagine and tyrosine derivatives. Preliminary peptidase purification by two-step ionic exchange showed the presence of two proteolytic fractions with molecular masses of approximately 24.0 kDa according to SDS-PAGE.